Banks, non-bank companies and stock exchange: do we know the relationship? - Ghimire, Binam; Gautam, Rishi; Karki, Dipesh; Sharma, Satish (Economics and Business Review, 2015)
This paper investigates the role played by the banking sector in founding, sustaining and developing stock exchange markets. The paper has constructed data on market capitalisation separately for banks and non-bank companies. We apply cointegration techniques developed by Engle and Granger [1987] and Johansen [1988] and we bootstrap the variables to examine the nature of relationship between the banks and stock markets. We found that banks have played an important role in the development of stock exchanges. Further, the empirical analysis made amongst ten developed and developing exchanges suggests a listing of non-bank companies important for development of stock markets. These findings have also been verified by analysing the data of an exchange not included in the test.